2003
DOI: 10.1097/01.ede.0000082001.05563.e0
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Risk Associated With Low-Level Benzene Exposure

Abstract: We found an excess risk of leukemia associated with cumulative benzene exposures and benzene exposure intensities that were considerably lower than reported in previous studies. No evidence was found of a threshold cumulative exposure below which there was no risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
178
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(188 citation statements)
references
References 21 publications
6
178
1
3
Order By: Relevance
“…A number of studies show elevated risks of chronic lymphocytic leukemia at relatively low levels of benzene exposure (Supplementary Table S1). The most notable is that of Glass et al (19), but others have also showed elevated risks including studies in the United Kingdom of petroleum distribution workers (20).…”
Section: Elevated Risks Of Chronic Lymphocytic Leukemiamentioning
confidence: 97%
“…A number of studies show elevated risks of chronic lymphocytic leukemia at relatively low levels of benzene exposure (Supplementary Table S1). The most notable is that of Glass et al (19), but others have also showed elevated risks including studies in the United Kingdom of petroleum distribution workers (20).…”
Section: Elevated Risks Of Chronic Lymphocytic Leukemiamentioning
confidence: 97%
“…Accordingly, it has been classified by the international agency for research on cancer (IRAC) (1982). There is an agreement that benzene can affect the hematopoietic system (10). It seems that all humans may be exposed to benzene.…”
Section: Introductionmentioning
confidence: 99%
“…Their results (Glass et al 2003;Table 4) showed that the four exposure groups between 1 and 16 ppm-years, compared to a baseline group with exposures up to 1 ppm-year, had odds ratios of 3.9, 6.1, 2.4 and 5.9. The two highest of these were declared statistically signiWcant at 5%, although there was no obvious trend with exposure.…”
Section: Resultsmentioning
confidence: 99%
“…More detailed nested case-control studies have attempted to address the question of risks of benzene at a greater level of detail, focussing on lymphatic-haematopoietic cancers as an outcome. Principal among these have been the studies of workers from the petroleum marketing and distribution workers from Canada , UK (Rushton and Romaniuk 1997), USA (Wong et al 1999) and Australia (Glass et al 2003). The results from the Wrst three studies were broadly similar in showing little evidence of an eVect of low benzene exposure.…”
Section: Introductionmentioning
confidence: 99%